A Survey on the position classification and salaries of librarians in special libraries in Metro Manila a follow-up study. - Oliva, Kathleen T.; Cruz, Ma. Divina P. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
In 1987, a survey on the position classification and salaries of librarians in special libraries in Metro Manila was done by a project team from the Institute of Library Science in the University of the Philippines Diliman. However, many changes have brought transformations in special libraries and librarians in the past years. With these changes, do the findings of the ILS survey still hold true today?.
Surveyed are 144 special libraries in Metro Manila from the staff of these libraries, 128 respondents are obtained. From the 128 questionnaires given, 103 are given back.
Figures show that most of the respondents are female, which is 83.5 percent of the population, 49.51 percent are married, and 21 of the respondents (20.39 percent) are from the 51-55 age group. Majority (83.5 percent) of the respondents are licensed librarians, and not all the positions held by the respondents require a Bachelor's degree in Library Science or Information Science or a Bachelor of Science in Education/Arts major in Library Science as a qualification. Most, with 66 responses (64.08 percent) of the positions held by special librarians in Metro Manila are under the librarian category. As a result, there are librarians in special libraries with different titles but the jobs they perform are unchanged.
The most frequently performed task in special libraries is bibliographic searching. Added to the list of activities performed by librarians are computer-related duties like maintaining the library software, cataloging with the use of LC On-line, developing database for library, and encoding. This illustrates that special librarians' responsibilities are continuously developing, and are constantly dealing with the new technology in information handling.
Most of the respondents are from the government sector and the generally received gross annual professional income is in the P100, 000 to 199,000-salary range. While two respondents who are working in private institutions receive a gross annual professional that as high as P 900,000 or above. This shows that the type of institution their library is in affects the respondents' salaries. The majority of the respondents are not satisfied with their salary. Several reasoned out that the pay is not enough because the relatively high cost of living.
Recommendations are encouragement of library personnel to attend seminars and training workshops to further develop computer literacy. Better compensation may also be a way to attract more individuals to stay in the profession. Innovations, like automation in libraries are also suggested for this not only improves the library's efficiency, but it also improves on the service and quality of the working lives of librarians.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Salaries -- Philippines -- Manila Metropolitan Area; Special libraries -- Philippines -- Manila Metropolitan Area